Pemeriksaan Kadar Total Protein dan Albumin Sebelum dan Sesudah Pemberian Makanan Tambahan Pada Balita Stunting di Kelurahan Penfui, Kota Kupang - Marni Tangkelangi; Supriati Wila Djami; Agnes Rantesalu (Universitas Kristen Indonesia Toraja, 2023)
Stunting is a condition that threatens the health of children as the nation's next generation. The prevalence of stunting in Penfui Subdistrict is high enough that it requires intervention through the OTA2S program using the method of Providing Supplementary Food (PMT) for 90 days to 21 stunted children but 10 people took part in the examination, parameters total protein and albumin as nutritional parameters can provide information regarding the nutritional status of stunted children. The results of total protein examination before and after PMT for all children were normal, however the albumin levels in all children before PMT were low, but after PMT 7 children were normal while 3 children were still low. Based on these findings, PMT is a good method to apply to reduce stunting rates.